Analisis Majas dalam Berita Politik pada Media Daring CNN Indonesia sebagai Modul Ajar Bahasa Indonesia untuk Materi Pidato Kelas IX SMP Berdasarkan Kurikulum Merdeka - Dzakhirotul Mufidah; Roni Nugraha Syafroni; M. Januar Ibnu Adham (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to identify and describe the types of figures of speech used in online political news on the CNN Indonesia website and to analyze their relevance as learning resources and Indonesian language teaching modules for ninth-grade junior high school speech students in accordance with the Merdeka Curriculum. The main problem in this study is the forms of figurative language use in CNN Indonesia's online political news and how this relates to the development of speech teaching materials. This study uses a descriptive qualitative method with a content analysis approach to deeply understand the phenomenon of figurative language use in news texts and its potential in educational contexts. Data collection techniques were carried out through reading, recording, and archiving online political news containing elements of figurative language. The results show that CNN Indonesia's political news contains various figures of speech (figurative comparison) and satire, including two hyperboles, six metaphors, one periphrase, one irony, one symbolic figure of speech, and one allegory. These findings indicate a richness of language styles in political news that can be utilized to develop students' language skills. A deep understanding of this figure of speech is essential in helping students critically interpret news texts and construct communicative speeches. Therefore, CNN Indonesia's online news, rich in figures of speech, is considered relevant as teaching material for Indonesian language learning in ninth-grade junior high school students within the Merdeka Curriculum framework.